U Thlen and the Nongshohnoh: Folklore, Experience, and Reality - Auswyn Winter Japang (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
The need to better understand the supernatural is an ever-engaging aspect of any enquiry into the matter due to the changing paradigms of time and space and the existence of numerous misconceptions and observations concerning the same. Such is a case of the legend of U Thlen and the nongshohnoh phenomenon of Meghalaya, a north-eastern state in the sovereign country of India. U Thlen, an evil mystical being, is described in Khasi legends and recounted in Khasi folklore as an entity thirsty for human blood and never satiated. He was, however, tricked and captured by the Khasi people but never ultimately destroyed. As an act of deception – of reward and mainly revenge, U Thlen promised people riches in exchange for human sacrifice. An existing belief is that U Thlen was adopted by a Khasi household which saw the beginning of the nongshohnoh or the “cut throat” phenomenon. The surrounding belief about the keeping of U Thlen functions on the basis of prevailing social notions that human sacrifice offered to U Thlen equates to riches. While the legend of U Thlen has witnessed transcendence from narratives to lived realities over an incredible part of the history of the Khasi people, the nongshohnoh phenomenon has seen its fair share of criticism with time as well. It is in this regard that this study aims to (re)look into this very phenomenon as a living reality of the Khasi society. This paper also aims to look at existing beliefs and disbeliefs in U Thlen and the nongshohnoh phenomenon in order to arrive at an understanding, proper to the contemporary setting of the Khasi society, in the twenty-first century.